HUBUNGAN PENGGUNAN BABY WALKER DENGAN PERKEMBANGAN MOTORIK KASAR PADA ANAKTOODLER DI DUSUN ARJOSARI DESAPAYUNGREJO KECAMATANKUTOREJO KABUPATENMOJOKERTO - Indatul Laili, Siti; Astutik, Nurwinda (JURNAL KEPERAWATAN SEHAT, 2016)
At toddler age growth rate began to decline and despite progress in motor development. To spur the development of gross motor movement, Parents use the Baby walker. The purpose of this research was to knowing relationship Use of the Baby Walker with gross motor development in Toodler in Arjosari hamlet, Payungrejo Village, Kutorejo District of Mojokerto. The research design used cross-sectional. The population in this research are all mothers and toodler in Arjosari hamlet, Payungrejo Village, Kutorejo District of Mojokerto a number of 20 respondents. The sampel was all mothers and toodler in Arjosari hamlet, Payungrejo Village, Kutorejo District of Mojokerto a number of 20 respondents. with total sampling teckhnic. The instrument in this research used denver II form and structured interviews sheet. The time of this research 23 Juni 2016. Analyzing data used was cross table frekuensi distribution. The results showed that Most respondents 12 respondents (60%) who did not use Baby Walker, normal gross motor development. This shows The process of running a baby with using a baby walker that is encourages like playing scooter, However child using just his feet. Where the state is the cause delays in the development of babies in motor skills and hinder the process goes on.Keyword:The use of the Baby Walker,gross motor development,Toodler